When in doubt, it's not out: Match format is associated with differences in elite-level cricket umpires' leg-before-wicket decisions. (November 2020) - Adie, Joshua M.; Renshaw, Ian; Polman, Remco; Thompson, Matthew B.; Mann, David L.
Abstract: Objectives: Contextual factors can influence the way sports officials apply unambiguous rules. The aim of this study was to better understand the leg-before-wicket (LBW) decision-making behaviour of elite cricket umpires and determine whether their behaviour changes according to the format of the game in which they are adjudicating. Methods: LBW decisions ( n  = 5578) from actual elite level cricket matches in Australia between 2009 and 2016 were analysed using a signal detection paradigm. Umpire sensitivity (A) and response bias (B) were compared to chance performance in three formats of the game: Four-day, One-day, and T20. Mixed effects models assessed sensitivity and response bias differences between match types. Results: Umpires were able to differentiate between "out" and "not out" appeals to a high standard but were conservative and had a bias to respond "not out" in all formats of the game. Umpires were less accurate in the shorter formats of the game, particularly T20 cricket and were also significantly more conservative in T20 compared to Four-day Matches. Conclusions: Cricket umpires are conservative and are highly accurate LBW decision makers. However, differences in their judgments were associated with different match formats. The unique task goals and contextual pressures afforded by the shorter formats of the game, particularly T20, may account for the observed performance differences we see here. Highlights: Cricket umpires are accurate, but conservative decision makers. Umpire decision performance changes across match types. Umpires are less accurate, and more conservative in the shortest format of the game (T20 cricket).